How H & R block has maximized its return on SOA counting on management infrastructure. - Carter, Fred (SOA webservices journal.)
Working with service-oriented applications is a lot like doing your taxes because : there's really no avoiding it, you need to keep track of a number of different factors, you must maintain a record of data to protect against audits and plan for the future, and you'd better catch any mistakes or you'll have a problem on your hands faster than you can spell "SOA."